Magnoflorine Ameliorates Inflammation and Fibrosis in Rats With Diabetic Nephropathy by Mediating the Stability of Lysine-Specific Demethylase 3A - Chang, Liang; Wang, Qi; Ju, Jiannan; Li, Yue; Cai, Qiao; Hao, Lirong; Zhou, Yang (Frontiers in Physiology, 2020)
Diabetic nephropathy (DN) represents one of the most devastating complications for patients with diabetes. The anti-diabetic activities of Magnoflorine (MF) was reported, with underlying mechanism unknown. Lysine-specific demethylase 3A (KDM3A) was identified in the renal injuries. In the current study, we investigated the functional role of MF in DN progression with the involvement of KDM3A. We reported that in the animal model of DN induced by streptozotocin (STZ) injection, MF attenuated inflammatory response and fibrosis in the kidneys. In cultured mesangial cells, MF similarly ameliorated abnormal proliferation and lowered the expression of inflammation- and fibrosis-related factors stimulated by high glucose treatment. Upon MF treatment, there was a decline in KDM3A-positive cells in renal tissues of rats, accompanying an augment in KDM3A ubiquitination. KDM3A upregulation in vitro by a proteasome inhibitor MG132 comparably dampened the inhibitory role of MF in inflammatory response and fibrosis. Further analyses revealed that MF increased transforming growth factor β-induced factor 1 (TGIF1) transcriptional activity by promoting ubiquitination and degradation of KDM3A, thus inhibiting the activation of TGF-β1/Smad2/3 signaling pathway. TGIF1 silencing weakened the repressive role of MF in mesangial cells as well. In conclusion, MF contributes to TGIF1 transcription via an epigenetic mechanism.